AAV‐mediated Gene Therapy for Hereditary Deafness: Progress and Perspectives - Liyan Zhang; Fangzhi Tan; Jieyu Qi; Yicheng Lu; Xiaohan Wang; Xuehan Yang; Xiangyan Chen; Xinru Zhang; Jinyi Fan; Yinyi Zhou; Li Peng; Nianci Li; et al. (Advanced Science)
Abstract Hereditary deafness is the most prevalent sensory deficit disorder, with over 100 identified deafness‐related genes. Clinical treatment options are currently limited to external devices like hearing aids and cochlear implants. Gene therapy has shown promising results in various genetic disorders and has emerged as a potential treatment for hereditary deafness. It has successfully restored hearing function in >20 types of genetic deafness model mice and can almost completely cure patients with hereditary autosomal recessvie deafness 9 (DFNB9) caused by the OTOFERLIN (OTOF) mutation, thus serving as a translational paradigm for gene therapy for other forms of genetic deafness. However, due to the complexity of the inner ear structure, the diverse nature of deafness genes, and variations in transduction efficiency among different types of inner ear cells targeted by adeno‐associated virus (AAV), precision gene therapy approaches are required for different genetic forms of deafness. This review provides a comprehensive overview of gene therapy for hereditary deafness, including preclinical studies and recent research advancements in this field as well as challenges associated with AAV‐mediated gene therapy.